Digital corporate culture as an element of the transformation of the organization in the context of digitalization - CHERNYAVSKAYA, SVETLANA ALEXANDROVNA; POLONKOEVA, FERDOUS YAKHIEVNA; DIUZHEVA, MARINA BORISOVNA; MUKHAMBETOVA, AMINA AKZATOVNA; TOKAYEVA, BELLA BATRAZOVNA (The journal of contemporary issues in business and government, 2021)
Transformational processes in modern organizations related to the digitalization of business systems require a deeper study of the digitalization process, taking into account organizational specifics. Often, the attempts to carry out a digital transformation of an organization are faced with serious problems, which are caused by the lack of understanding of the transformational process system by the management, and by the fact that it should affect and change not only the material, but also the organizational, and the human capital of the business system. The existing confusion between "digital strategy" and "digital transformation strategy" categories leads to wrong management decisions, which entail an avalanche of risks and losses when trying to transform organizational system digitally. Modern studies of Russian organizations show that the misunderstanding of the "digital transformation" category by management leads to the inhibition of digital processes, and the unwillingness of the organization staff to change their working methods and increase of digital competencies in accordance with the digital transformation strategy reduces almost to zero all attempts to transform the organization in accordance with the requirements of the digital economy by senior management. The study revealed that in order to get the greatest effect from the digital transformation of an organization, it is necessary to develop clearly a strategy for the digital transformation of the company, increase the digital competencies of staff, change the organizational culture towards the digital type of organizational culture, create a team of digitalization leaders in the organization, attract and retain talents. Digitalization changes the process of information exchange between people and organizations, and also forms a system of digital organizational culture that contributes to the implementation of transformational digital processes. The success of transformational digital processes can be assessed using the organization digital maturity model, as well as a special electronic readiness index (E - Readiness index). The analysis and synthesis of special literature on the issues under consideration suggests the need to take a fresh look and evaluate the problems of digital transformation of business systems during the transition to a digital economy.